Dynamic Causality between CO2 Emissions, Urbanization and Economic Growth in India and South Africa - Singh, Gopal Ji; Singh, Pawan Kumar; Kumar, Rakesh; Aman, Arfia; Alam, Imran; Fatma, Ramla; Ansari, Shoaib (International Journal of Energy Economics and Policy, 2025)
This study investigates the interplay between urbanization, economic growth, and carbon dioxide emissions in South Africa and India, highlighting its significance for sustainable environmental management. Using autoregressive distributed lag (ARDL) bound testing and drawing on ecological modernization and urban environmental transition theories, the analysis covers the period 1971-2019. The results reveal a long-term relationship among urbanization, economic growth, and emissions in both countries. In South Africa, urbanization contributes to a reduction in carbon dioxide emissions, whereas in India, it negatively affects environmental quality and does not significantly mitigate pollution. Economic growth, however, consistently increases emissions over time in both nations. The study further finds that urban expansion predominantly drives emissions in South Africa, while economic growth has a stronger influence in India. These findings underscore the need for integrated urban and environmental planning, along with stable environmental regulations, to achieve long-term ecological benefits and align development with sustainable environmental objectives.